APLIKASI PEMBELAJARAN PENGENALAN HURUF MENGGUNAKAN AUGMENTED REALITY: artikel - shiviana; Fitri Yanti (PT Triputra Sejahtera Prima, 2024)
Beginning reading is the initial stage in learning to read which is focused on recognizing symbols or signs related to letters so that it becomes the foundation so that children can continue to the beginning reading stage. One technology that is currently popular is Augmented Reality (AR) technology which combines two-dimensional or three-dimensional virtual worlds into a real environment.